(3bQI GdYjf aj GdaJM hGdEeGdI hHjf GddaXjfs - (3Ydj Hf YKeGf Hf eMeO Hf CMeO, CHh GdHbGA GdYPQj, hjYQa H (B: (3GHf GdbGUM,J (B801 (3g` s
(3ChdgG (B:s
(3bGd CHh GdHbGA Ydi Hf YKeGf GdbGUM GdYPQi CeG HYO MeO QH GdYGdejf aEf gPg QSGdI SejJgG bQI GdYjf hLeYJ ajgG GdeTghQ ef GdaJM hGdEeGdI hHjf GddaXjf eYkG s
(3BNQgG (B:s
(3hdjS ai ShQI GdENdGU hGdadb TF ef GdEeGdI hgPG BNQ eG LeYJ hHGddg GdJhajb s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3ejRJ GdShQ hGdbQGAGJ HGdeOGO GdCMeQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B727s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1325s
Keywords: (3GdbQGAGJ hGdJLhjOs